Pengaruh Return on Equity, Return on Asset, dan Firm Size Terhadap Tingkat Underpricing Saham Perusahaan yang Melakukan Go-Public di Bursa Efek Indonesia Periode 2016 - 2019 - Muhamad Syahwildan; Muhamad Aminudin (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The purpose of this study was to analyze the effect of financial and non-financial ratios in the form of return on equity, return on assets, and firm size on the level of underpricing. The hypothesis is tested using multiple linear regression analysis methods. The data used in this research are annual financial report data, opening stock price on the first trading day, and closing stock price on the first trading day. Eviews 10 is an analytical tool used in research. Sampling in this study used a purposive sampling method and obtained data from 75 companies from 160 companies that carried out the Go-public process on the Indonesian Stock Exchange for the period 2016-2019. The analytical method used is quantitative methods. The results of this study indicate that the return on equity (ROE) and return on assets (ROA) variables do not have a significant effect on the level of underpricing of the shares of companies that go public on the Indonesian Stock Exchange in the 2016-2019 period, while the firm size variable has a significant effect. on the level of underpricing of shares of companies that went public on the Indonesian stock exchange for the 2016-2019 period